2012
DOI: 10.1016/j.biocel.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cancer imaging: Gene transcription-based imaging and therapeutic systems

Abstract: Molecular-genetic imaging of cancer is in its infancy. Over the past decade gene reporter systems have been optimized in preclinical models and some have found their way into the clinic. The search is on to find the best combination of gene delivery vehicle and reporter imaging system that can be translated safely and quickly. The goal is to have a combination that can detect a wide variety of cancers with high sensitivity and specificity in a way that rivals the current clinical standard, positron emission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The latter can be accomplished by using a target‐selective promoter to drive the expression of a reporter following systemic delivery of a reporter plasmid. Many promoters of genes with elevated expression in human cancers have been examined as potential cancer‐specific promoters, but most are active only in cancers of certain tissues of origin . The optimal promoters for cancer‐specific, molecular‐genetic imaging would be active in a variety of human cancers, while remaining minimally active or silent in normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The latter can be accomplished by using a target‐selective promoter to drive the expression of a reporter following systemic delivery of a reporter plasmid. Many promoters of genes with elevated expression in human cancers have been examined as potential cancer‐specific promoters, but most are active only in cancers of certain tissues of origin . The optimal promoters for cancer‐specific, molecular‐genetic imaging would be active in a variety of human cancers, while remaining minimally active or silent in normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…An inherent constraint to the development of conventional injectable agents is that the details of synthesizing, labeling and validating a new and different ligand for every new receptor or protein of interest impose long cycle times on development. However, genetically-encoded reporters offer more modular tools for preclinical research, which once cloned into appropriate vectors and biologically confirmed, can be quickly applied to a broad array of applications with minimal modification (22, 24). While genetically-encoded imaging reporters are under development for use in humans, the potential for immunogenicity and transduction inefficiencies raise unique challenges (25).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imaging techniques target particular cancerassociated cell markers either on the cell surface or intracellular markers such as intracellular signaling molecules or may even target gene expression [53][54][55]. Examples of such markers in ovarian cancer are folate receptor α and CA125.…”
Section: Imaging Of Ovarian Cancermentioning
confidence: 99%